PTPN11 in cartilage development, adult homeostasis, and diseases - Wentian Yang; Véronique Lefebvre (Bone Research)
Abstract The SH2 domain-containing protein tyrosine phosphatase 2 (SHP2, also known as PTP2C), encoded by PTPN11, is ubiquitously expressed and has context-specific effects. It promotes RAS/MAPK signaling downstream of receptor tyrosine kinases, cytokine receptors, and extracellular matrix proteins, and was shown in various lineages to modulate cell survival, proliferation, differentiation, and migration. Over the past decade, PTPN11 inactivation in chondrocytes was found to cause metachondromatosis, a rare disorder characterized by multiple enchondromas and osteochondroma-like lesions. Moreover, SHP2 inhibition was found to mitigate osteoarthritis pathogenesis in mice, and abundant but incomplete evidence suggests that SHP2 is crucial for cartilage development and adult homeostasis, during which its expression and activity are tightly regulated transcriptionally and posttranslationally, and by varying sets of functional partners. Fully uncovering SHP2 actions and regulation in chondrocytes is thus fundamental to understanding the mechanisms underlying both rare and common cartilage diseases and to designing effective disease treatments. We here review current knowledge, highlight recent discoveries and controversies, and propose new research directions to answer remaining questions.